USAHA PENGGEMUKAN SAPI SIMMENTAL PERANAKAN ONGOLE DENGAN APLIKASI BAHAN DASAR Indigofera, sp. - Wily Andani; Wiwik Ambarsari; Yudhi Mahmud; Asep Suherman (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2022)
This study aim to know average of weight gain of SIMPO cattle by aplication Indigofera, sp., bran rice and ammoniated fermented rice straw and SIMPO cattle with ration of the breeder’s habits, total cost of production, revenue, business profits, R/C, and rentability. Fattening cattle SIMPO in the Livestock Group “Tunggal Rasa”. This research was conducted since May to August 2017 in the Livestock Group “Tunggal Rasa” in Majasari Village Sliyeg District Indramayu Regency. Methods of research using survey method and experiment method with descriptive approach. Sample were taken purposively with 2 people. The result were obtained average of increased weight of cattle SIMPO by providing feed combination of rice bran, Indigofera, sp., and ammoniated fermented rice straw for 3 months was 64.5 kg/head, average of total production cost was IDR 13,386,904.20, average of revenue was IDR 18,585,000.00, average of profit was IDR 5,198,095.80, average of R/C value was 1.39, and average of rentability was 38.84%, while the average weight gain of beef cattle SIMPO by providing feed of the breeder’s habits, that was used fresh straw, fresh grass, rice bran, molasses, and salt for 3 months was 52.25 kg/head, average of total production cost was IDR 14,272,652.96, average of revenue was IDR 18,135,000.00, average of profit was IDR 3,862,347.04, average of R/C value was 1.27, and average of rentability was 27.09%.